Diagnosing and Remediating Clinical Reasoning Difficulties: A Faculty Development Workshop - Adam Weinstein; Shanu Gupta; Roshini Pinto-Powell; Jennifer Jackson; Joel Appel; Danielle Roussel; Michelle Daniel (Association of American Medical Colleges, 2017)
Introduction Clinical reasoning is a complex cognitive process that involves multiple steps. Diagnosing and remediating clinical reasoning difficulties requires faculty to have an understanding of the cognitive theory behind clinical reasoning, familiarity with terminology, and a framework to identify different domains of struggle in their learners. Published resources on faculty development to diagnose and remediate clinical reasoning difficulties are limited. We created and implemented a workshop to assist faculty in developing these skills based on the five-domain framework described by Audétat, Laurin, and Sanche. This workshop provides all the materials needed to replicate this training with faculty at other institutions. Methods The workshop consists of a didactic component and case-based active learning in small groups. Each case focuses on different domains of clinical reasoning difficulties and targets different learner levels (preclinical medical students through residents). The workshop was given in multiple venues in 2016 and 2017. Results Participants reported the session was valuable (4.71/5.0), the facilitators were effective (4.5/5.0), and the objectives were met (4.28/5.0). They highlighted the strengths of the interactive format, the framework to diagnose and remediate clinical reasoning difficulties, and the excellent take-home resources. They suggested more time for the workshop, revision of cases to better highlight difficulties, and refinement of instructions to approach the cases. These suggestions were incorporated into the current iteration of the workshop. Discussion We successfully implemented a workshop for diagnosing and remediating clinical reasoning difficulties in multiple venues. The sessions were diverse in terms of faculty participants and learner groups addressed.